Measurement of the forward Z boson production cross-section in pp collisions at √s=7 TeV - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; et al. (Journal of high energy physics, 2015)
A measurement of the production cross-section for Z bosons that decay to muons is presented. The data were recorded by the LHCb detector during pp collisions at a centre-of-mass energy of 7 TeV, and correspond to an integrated luminosity of 1.0 fb−1. The cross-section is measured for muons in the pseudorapidity range 2.0 < η < 4.5 with transverse momenta pT > 20 GeV/c. The dimuon mass is restricted to 60 < Mμ+μ− < 120 GeV/c2. The measured cross-section isσZ→μ+μ−=76.0±0.3±0.5±1.0±1.3pb.
Im Titel steht "s" unter dem Wurzelzeichen
The LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, E. Gersabeck, L. Grillo, O. Grünberg, X. Han, S. Hansmann-Menzemer, A. Jaeger, K. Matthieu, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, C. Voss, S. Wandernoth, D. Wiedner, A. Zhelezov [und 668 weitere]
Gesehen am 16.12.2020